PENERAPAN STRATEGI PEMBELAJARAN INKUIRI DIPADUKAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN BIOLOGI SISWA KELAS VII D SMP N 1 JATEN - Rachmah, Fitriyana; Sajidan, Sajidan; Indrowati, Meti (Pendidikan Biologi, 2012)
ABSTRACT ? The aim of this research is improve quality of biology learning for conditioning class, student attitude in class, the performance of teacher and student motivation of learning in student class VII-D 1st Junior High School Of Jaten through the application of strategies for inquiry learning combined audio visual media. This research was classroom action research with planning, action, observation, and reflection steps. Data was collected using questionnaire, observation, and interview. The validation of data using method and observer triangulation techniques. The data analyzed by descriptive. The result in cycles I describes that mean of observation data in conditioning class indicators are 70,20%, students? attitudes in class are 62,77%, performance of teachers in the learning are 80% and students motivation in learning are 68,18%. For the questionnaire, observation data in conditioning class indicators are 74,53%, students? attitudes in class are 74,13%, and students motivation in learning are 74,38%. The result in cycles II describes that mean of observation data in conditioning class indicators are 80,81%, students? attitudes in class are 80.09%, performance of teachers in the learning are 96,67% and student motivation in learning are 83,71%. For the questionnaire, observation data in conditioning class indicators are 83,87%, students? attitudes in class are 82,49%, and students motivation in learning are 79,43%. In addition, this research also uses interview to know effect of research in quality of biology learning. The result of interview shows that students' attitudes more positive, students motivation more increase and classroom climate more conducive on learning activities. The conclusion of research describes that the combination of audio visual media in inquiry learning strategies can improve quality of biology learning for conditioning class, students' attitudes, performance of teachers in the learning and motivation of  learning in student class VII-D in 1st junior high school of jaten. Keywords: inquiry learning strategies, audio visual media, quality of biology learning.